Data from: The significance of retention trees for survival of ectomycorrhizal fungi in clear‐cut Scots pine forests - Sterkenburg, Erica; Clemmensen, Karina E.; Lindahl, Björn D.; Dahlberg, Anders (Zenodo, 2019)
1. Forestry with short stand generations and simplified forest structures has markedly af-fected forest biodiversity. One group of organisms adversely affected by clear-cutting is ectomycorrhizal (ECM) fungi, as they are associated with the roots of living trees. Retention forestry is a way of reducing logging impacts and enhancing biodiversity conservation. In-creasing the proportion of trees retained at harvest may improve ECM fungal diversity. 2. We investigated the potential for life-boating of ECM fungi through the harvesting phase in an experimental field study in a 190 years old Scots pine forest in northern Sweden. The experiment comprised four levels of tree retention – unlogged forest, plots with 60% or 30% of evenly distributed trees retained, and clear-cuts without retained trees. We sampled soils and determined identities, frequencies and relative abundances of ECM fungal species dur-ing three years following logging through the use of high-throughput sequencing of ampli-fied ITS2 markers. 3. We identified 151 ECM fungal species, with the five most abundant species accounting for 50% of the total ECM fungal amplicons. Three years after harvesting, the proportion of ECM sequences in the total amplicon pool had decreased proportionally to the extent of tree removal. In clear-cuts ECM fungal relative abundance had decreased by 95%, while ECM fungal species richness had declined by 75%, compared to unlogged plots. 4. Tree retention enabled maintenance of the most frequent ECM species, while more lowly abundant species were progressively lost at random with increasing level of tree removal. Five of the most frequent ECM fungal species remained present after clear-cutting, probably associated with pine seedlings. 5. Synthesis and applications. Tree retention can moderate short-term and potentially also long-term logging impacts on ectomycorrhizal (ECM) fungi. Local ECM fungal diversity is preserved in proportion to the amount of retained trees. Abundant species may be largely maintained, even by low ...